2009
DOI: 10.1111/j.1937-5956.2009.01028.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Ordering Policies for Stochastic Inventory Problems with Observed Information Delays

Abstract: Information delays exist in an inventory system when it takes time to collect, process, validate, and transmit inventory/demand data. A general framework is developed in this paper to describe information flows in an inventory system with information delays. We characterize the sufficient statistics for making optimal decisions. When the ordering cost is linear, the optimality of a state‐dependent base‐stock policy is established even when information flows are allowed to cross over time. Additional insights i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Recent supply chain models have often focused on contract-theoretic analysis of organizational decisions based on information asymmetry (Bensoussan et al 2009). 6 At the growth stage, OM articles are typically dynamic programming formulations that explore the management of capacity growth under a variety of contexts ranging from loss of aggregate productivity due to hiring (Anderson 2001), technological change (Li et al 2003), and long lead times needed to acquire capacity (Gaimon and Burgess 2003).…”
Section: Operations Management Researchmentioning
confidence: 99%
“…Recent supply chain models have often focused on contract-theoretic analysis of organizational decisions based on information asymmetry (Bensoussan et al 2009). 6 At the growth stage, OM articles are typically dynamic programming formulations that explore the management of capacity growth under a variety of contexts ranging from loss of aggregate productivity due to hiring (Anderson 2001), technological change (Li et al 2003), and long lead times needed to acquire capacity (Gaimon and Burgess 2003).…”
Section: Operations Management Researchmentioning
confidence: 99%
“…It takes time to collect, process, validate, and transmit inventory/demand data; therefore, information delays are expected in inventory systems (Bensoussan et al., 2009). Consequently, the most recent inventory information available to the inventory manager is dated when making ordering decisions.…”
Section: Discounted Cost Criterionmentioning
confidence: 99%
“…Furthermore, one can write the evolution of the conditional probability in terms of its current value, the current order, and the current observation. However, there are no longer simple optimal policies except in cases of information delay reported in Bensoussan et al (2009) where modified base stock and (s; S) policies are shown to be optimal.…”
Section: Incomplete Inventory Information Models (I3)mentioning
confidence: 99%